High School, the low teaching: Geography of the refusal of a right - Luiz Carlos Gil Esteves (Arizona State University, 2018)
Who are the victims of not abiding with the laws that determine the State's offer of compulsory and free education to all young people from 15 to 17 years in Brazil? Starting with this question, based on Pnad/IBGE data from 2001 to 2015, this article delineates a brief profile of these individuals, whose contingent comprises more than 1.5 million young people. In absolute numbers, they belong to the poorest part of society, are predominantly blacks, and residents of urban areas of the Northeast and Southeast regions, especially in SP, MG and BA. In percentage terms, they are also the poorest and black, live in rural areas of the Northeast, Midwest and North, in the States of MS, RO and MT. Another finding of the survey indicates that neither the legislation requiring the mandatory bid of such young people nor the Fundeb implementation were able to accelerate the pace of growth of enrollments during the period. Despite this, there are important indicators of inclusion, clearly expressed by the incorporation of portions of the population historically more distant from school, such as the young people belonging to the poorest Brazilian population, race/color black and residents in rural areas.